Aspectos clínico-laboratoriais de pacientes com formas graves de dengue em Fortaleza, Ce - Rolim, Meire Luce Moreira (2005)
Dengue is an acute viral disease of varied clinical spectrum and of great epidemiological importance in Brazil, including Ceará being Fortaleza a district in which the magnitude of the problem consists in concentrating a larger number of severe cases of the state. This research is about a descriptive study and prospective of secondary data of 103 cases of dengue registered in Fortaleza. The general objective was to describe profile of the platelets counting and of the hematócrito correlating them with the clinical evolution and type immunological response of patients with severe cases of dengue in three hospitals this district in 2003. The data were collected from hospital files and were included only the cases confirmed by serology for the virus of dengue by ELISA technique. For statistic analysis we used the non-parametrical tests of Wilcoxon post addings. As a result we found out that: the low value of platelets (trombocytopenia) was known to all analyzed patients (the minimum value were varied from 13.000/mm³ to 75.000/mm³), with the decrease in the platelets counting from the first day in which the exam was done being more evident from the fifth to the eighth day of the evolution of the disease. The value of the hematócrito was instable during the days of the evolution of the disease with a higher average from the third to the sixth day. The maximum average value was of 44,5% presented by only 25% of the patients of the sub-sample. The first hemorrhagic manifestation occurred on the first day of the symptoms, being more elevated from the fifth to the seventh day, but after the tenth day of the disease no patient presented this manifestation. It was not established any relation between Trombocytopenia and hemorrhagic manifestations. There was no relation between secondary response and trombocytopenia nor with hemoconcentration but it was significant the relation with hemorrhagic or alert sign of hemoconcentration for the patients of the sub-sample. Primary immunological response to the virus of dengue was more present (72,3%) than the secondary response (27,7%). Unusual cases of dengue were identified in 06 (5,8%) of the patients of the sample, and probably were the most severe cases. The importance of these results consists of the available data analysis, allowing the knowledge of the severe forms of dengue in order to identify the early signs of gravity and the best way of monitoring. Nevertheless it is still necessary to know better the dynamic of the illness in our environment. Moreover it is necessary to assure the effective control of the illness, which is a problem of great seriousness especially in the big centers of our country.